Prices in Motion: Towards a Schumpeterian Price Theory - Bloch, Harry (2016)
To Schumpeter, endogenous development is an essential characteristic of capitalism that disrupts the equilibrium of the circular flow of the economy. Price equilibrium in the circular flow is displaced by an analysis of prices in motion. The diversion of productive inputs from their existing employment through competition from entrepreneurs and the process of creative destruction both impact on prices throughout the economy and generate business cycles. While Schumpeter's theory of the business cycle and, implicitly, his price theory, have been heavily criticized, this article suggests a way forward to a revised theory of prices in motion.